2014
DOI: 10.17795/jjhr-23228
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Pyrene-Contaminated Soils Using Biosurfactant

Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) are persistence organic chemicals with proved carcinogenic and mutagenic hazards. These compounds are usually adsorbed in soils in vicinity of oil and gas industries. Bioremediation of PAHs contaminated soils is difficult due to hydrophobic nature of PAHs. Objectives: The main purpose of the current study was to determine the pyrene removal efficiency in synthetically contaminated soil, using biosurfactant. Materials and Methods: Four pure bacterial strains c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The rate of fluoranthene mineralization was above 50% (using 500 μg ml −1 of alasan), with an attendant significant increase in the rate of phenanthrene mineralization by Sphingomonas paucimobilis EPA505. Similarly, Jorfi et al [120] recorded 86.4% of pyrene degradation with an initial concentration of 500 mg/kg. Complete degradation of aromatic hydrocarbon was demonstrated using a chemical surfactant (FinasolOSR-5) combined with a trehalose lipid biosurfactant [121].…”
Section: Biosurfactants For Environmental Remediationmentioning
confidence: 91%
See 1 more Smart Citation
“…The rate of fluoranthene mineralization was above 50% (using 500 μg ml −1 of alasan), with an attendant significant increase in the rate of phenanthrene mineralization by Sphingomonas paucimobilis EPA505. Similarly, Jorfi et al [120] recorded 86.4% of pyrene degradation with an initial concentration of 500 mg/kg. Complete degradation of aromatic hydrocarbon was demonstrated using a chemical surfactant (FinasolOSR-5) combined with a trehalose lipid biosurfactant [121].…”
Section: Biosurfactants For Environmental Remediationmentioning
confidence: 91%
“…Though subject to more robust research, it has been reported that rhamnolipids produced by the Pseudomonas aeruginosa strain specifically degrade hexadecane, indicating that a specific biosurfactant does degrade a particular type of hydrocarbon [108]. Rhamnolipid has been reported in the remediation of diverse kinds of hydrocarbon more than any other biosurfactant [120].…”
Section: Biosurfactants For Environmental Remediationmentioning
confidence: 99%
“…Further, Bustamante et al [119] noted the influence of alasan on the biodegradation of polyaromatic hydrocarbons (PAHs): the rate of fluoranthene mineralization was above 50% (using 500 μg ml -1 of alasan) with an attendant significant increase in the rate of phenanthrene mineralization by Sphingomonas paucimobilis EPA505. Similarly, Jorfi et al [120] recorded 86.4% of pyrene degradation with an initial concentration of 500 mg/kg. Complete degradation of aromatic hydrocarbon was demonstrated using a chemical surfactant (FinasolOSR-5) combined with trehalose lipid biosurfactant [121].…”
Section: Bioremediation Of Hydrocarbon Contaminated Soilmentioning
confidence: 85%
“…Though subject to more robust research, it has been reported that rhamnolipids produced by Pseudomonas aeruginosa strain specifically degrade hexadecane, indicating that specific biosurfactant does degrade a particular type of hydrocarbon [108]. Rhamnolipid has been reported in the remediation of diverse kinds of hydrocarbon more than any other biosurfactant [120].…”
Section: Bioremediation Of Hydrocarbon Contaminated Soilmentioning
confidence: 99%
See 1 more Smart Citation